Commentaries on "Evaluating the Geographic in GIS". - Warren, Stacy; Harris, Trevor; Goodchild, Michael; Solís, Patricia (Geographical Review, 2019)
In this article, four geographers who are also GIS practitioners critique "Evaluating the Geographic in GIS." Sparked by the arguments in that article, they pose fundamental questions about how geography can best contribute to GIS practices.